Lessons Learned from a Small Pediatric Continuous Renal Replacement Therapy Program - Tanya Holt; Olivia Griffin; Amelie Cyr; Rebecca Brockman; Laura Wihak; Gregory Hansen (Critical Care Research and Practice)
Continuous renal replacement therapy (CRRT) has become a pillar of care in pediatric intensive care units (PICUs) over the past few decades. Quality indicators (QIs) have been evaluated that reflect safe and accountable CRRT. However, there is a paucity of data on outcomes and QIs in smaller-volume CRRT programming. The purpose of this retrospective study was to evaluate the efficiencies, effectiveness, and outcomes of a small-volume CRRT program. Eighty-two patients received CRRT over a 13-year period, and 79% survived to discharge. Sepsis or nonseptic shock (n = 11 (22%) versus n = 6 (50%); p value = 0.004) and time to CRRT initiation after PICU admission (1.1 versus 5.0 days; p value = 0.005) were independent predictors for mortality. The program also had positive outcomes for QIs related to CRRT efficiency and time of initiation, dosing delivery, and rate of adverse events. This study is important as it illustrates the opportunity that smaller centers have to initiate CRRT programming and provide safe and effective care.